Foreign relations of Trinidad and Tobago (1962-2000) : the case of a small state in the global arena - Basdeo, Sahadeo (Lexicon Trinidad Ltd San JuanTT, 2001)
Reviews Trinidad and Tobago's foreign relations during four administrations viz. those of Eric Williams (1962-1981); George Chambers (1981-1986); A.N.R. Robinson (1986-1991; and Patrick Manning (1991-1995).